2022
DOI: 10.3390/antiox11081458
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Lilium Plants in Cosmetics: A Comprehensive Review Based on Research Papers and Patents

Abstract: The application of cosmetics is indispensable in our current society. In recent years, with an increasing awareness of the long-term health benefits of naturally sourced ingredients, plant-based cosmetic products have gained increasing attention. Lilium belongs to the Liliaceae family, which is one of the main plant families used in cosmetics for skin care treatment. A large number of studies have shown that Lilium plants are rich in components such as phenolic acids, flavonoids, and polysaccharides, with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…It is supposed that the presence of varying amounts of polysaccharides or other secondary metabolites from lily bulb extract exerts greater antioxidant potentials that mask the effects of phenolics or that the specific phenolic species present in the system are not adequately quantifiable [ 12 , 22 ]. According to reports in the published literature, polysaccharides, which make up 10–36% of the dry weight of the bulb, are one of the richest carbohydrate components in the lily and have potent antioxidant activities as assessed by DPPH [ 23 , 24 ]. A recent study showed a significant positive correlation between some alkaloids, terpenoids, and other substances in lily, which may be important antioxidants [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that the presence of varying amounts of polysaccharides or other secondary metabolites from lily bulb extract exerts greater antioxidant potentials that mask the effects of phenolics or that the specific phenolic species present in the system are not adequately quantifiable [ 12 , 22 ]. According to reports in the published literature, polysaccharides, which make up 10–36% of the dry weight of the bulb, are one of the richest carbohydrate components in the lily and have potent antioxidant activities as assessed by DPPH [ 23 , 24 ]. A recent study showed a significant positive correlation between some alkaloids, terpenoids, and other substances in lily, which may be important antioxidants [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…771–773). It is an ornamental flower, frequently cultivated as a house plant (potted plant) or garden plant for its unique esthetic, medicinal, and edible values [ 23 , 60 ].…”
Section: Plants Involved and Their Descriptionmentioning
confidence: 99%
“…Based on the abundance of these bioactive substances, cosmetic ingredients derived from Lilium plants have been utilized for anti-aging, radiation protection, moisturization, acne treatment, and hair growth promotion. However, no study has investigated the anti-melanogenic effects of L. lancifolium [62]. Prior to assessing the anti-melanogenic effects of LRE, its potential cytotoxicity was examined in B16F10 cells (Figure 1A).…”
Section: Effects Of Lre On Cell Viability and Melanogenesis In B16f10...mentioning
confidence: 99%